Removal of Esophageal Variceal Bands to Salvage Complete Esophageal Obstruction - Jalil, Ala’ A Abdel (Clin Endosc, 2018)
Esophageal varices develop in almost half of the patients with cirrhosis, and variceal hemorrhage constitutes an ominous sign with an increased risk of mortality. Variceal banding is considered an effective and mostly safe measure for primary and secondary prophylaxis. Although adverse events related to banding including dysphagia, stricture formation, bleeding, and ligation-induced ulcers have been described, complete esophageal obstruction is rare, with only 10 reported cases in the literature. Among those cases, 6 were managed conservatively; 1 patient had esophageal intraluminal dissection from an attempt to remove the bands using biopsy forceps but ultimately recovered with conservative management. Three patients developed strictures following removal of the bands, requiring repeated sessions of dilation therapy. We report on a patient who developed absolute dysphagia and complete esophageal obstruction after variceal banding. We successfully used the endoloop cutter hook to release the bands intact and restore luminal integrity.